Method for improving toughness of additive manufacturing 18Ni300 die steel
By adding high-melting spherical metal or alloy powder to the 18Ni300 mold steel and using laser powder bed melting process and heat treatment technology, the gamma austenite content and interface combination effect of the material are improved, and the problem of insufficient toughness of the 18Ni300 mold steel is solved, and the effect of improving toughness while ensuring strength is achieved.
Patent Information
- Application Number
- CN202510064606.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-15
- Publication Date
- 2025-04-15
AI Technical Summary
18Ni300 mold steel has low toughness after additive manufacturing, and its elongation after break is usually less than 5%, which seriously restricts its practical application.
By adding 3% to 6% by weight of high melting point spherical metal or alloy powder to 18Ni300 mold steel, additive manufacturing is performed using a laser powder bed melting process and heat treatment is carried out to improve the gamma austenite content of the material and the interface bonding effect of partially melted particles.
The toughness of 18Ni300 mold steel has been significantly improved, and the elongation and impact toughness after break have been significantly improved. At the same time, the tensile strength and yield strength can also be maintained at a high range, solving the problem of poor plasticity of mold steel.
Smart Images

Figure CN119819943A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of metal materials, and in particular to a method for improving the toughness of 18Ni300 die steel produced by additive manufacturing. Background Art
[0002] 18Ni series martensitic aging steel represented by 18Ni300 is widely used in mold manufacturing in the automotive, electronics, home appliances, plastics, rubber and other industries. It mainly relies on the dispersion and precipitation of nano-scale intermetallic compounds (Ni3Ti, Fe2Mo, NiAl) of alloying elements such as Co and Mo during aging treatment to achieve strengthening effect. The room temperature tensile strength of 18Ni300 mold steel manufactured by laser powder bed melting additive manufacturing can reach 1900MPa~2000MPa after heat treatment, but its toughness is too low, and the elongation after fracture is usually less than 5%, which seriously restricts practical application.
[0003] Therefore, for 18Ni300 martensitic die steel, it is urgent to find a method to improve the toughness while ensuring the strength.
[0004] In view of this, the present invention is proposed. Summary of the invention
[0005] The object of the present invention is to provide a method for improving the toughness of 18Ni300 die steel in additive manufacturing, so as to solve or improve the above-mentioned technical problems.
[0006] The present invention can be implemented like this:
[0007] In a first aspect, the present invention provides a method for preparing 18Ni300 die steel, comprising the following steps:
[0008] Additive manufacturing of composite powders using laser powder bed fusion followed by heat treatment;
[0009] The composite powder comprises 3wt% to 6wt% of high melting point spherical metal or alloy powder and the balance is 18Ni300 powder; the high melting point spherical metal or alloy powder comprises pure Mo powder or WC powder with sphericity not less than 95%.
[0010] In an optional embodiment, the composite powder consists of 18Ni300 powder and pure Mo powder with a sphericity of not less than 95%.
[0011] In an optional embodiment, the particle sizes of the 18Ni300 powder and the high-melting-point spherical metal or alloy powder are independently 15 μm to 53 μm.
[0012] In an optional embodiment, the conditions for additive manufacturing include: laser power of 150W to 350W, scanning speed of 700mm / s to 1500mm / s, scanning spacing of 0.06mm to 0.10mm, and powder thickness of 0.03mm to 0.05mm.
[0013] In an optional embodiment, the heat treatment includes: treating at 470° C. to 530° C. for 4 h to 8 h, followed by air cooling.
[0014] In an optional embodiment, the heat treatment includes: treating at 490° C. for 6 hours, followed by air cooling.
[0015] In an optional embodiment, the 18Ni300 die steel contains both γ austenite and α martensite, wherein the content of γ austenite is not less than 9%.
[0016] In an optional embodiment, the content of γ-austenite in the 18Ni300 die steel is 9.3% to 17.1%.
[0017] In an optional embodiment, the room temperature elongation of 18Ni300 die steel is 7.6% to 12.2%, and the impact toughness is 24.4 J / cm 2 ~37.5J / cm 2 , the tensile strength is 1612MPa~1958MPa, and the yield strength is 1403MPa~1823MPa.
[0018] The beneficial effects of the present invention include:
[0019] The present invention creatively proposes to improve the toughness of 18Ni300 die steel for additive manufacturing by adding high-melting-point spherical metal or alloy powder. By compounding 18Ni300 powder with high-melting-point spherical metal or alloy powder in a specific ratio, and then melting and heat treating it in a laser powder bed, the γ-austenite content in the material microstructure is significantly increased, and the toughness of the material is improved. At the same time, there is a certain amount of partially melted spherical particles in the microstructure, and the interface between it and the matrix presents a good metallurgical bonding (diffusion type), and a large number of nano-scale strengthening phases are precipitated, which is conducive to ensuring the high strength of the material.
[0020] Compared with the conventional additively manufactured 18Ni300 die steel, the γ-austenite content in the 18Ni300 die steel provided by the present invention is significantly increased and the α-martensite content is reduced, the elongation after fracture and the impact toughness are significantly improved, while the tensile strength and yield strength can also be maintained in a high range, that is, it can have higher toughness while ensuring strength, and can effectively solve the problem of poor plasticity of the die steel. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0022] Figure 1 Scanning electron microscope images of 18Ni300 die steel powder used in various embodiments and comparative examples of the present invention;
[0023] Figure 2 Scanning electron microscope images of Mo powder used in various embodiments and comparative examples of the present invention;
[0024] Figure 3 Scanning electron microscope images of WC powder used in various embodiments and comparative examples of the present invention;
[0025] Figure 4 X-ray diffraction spectra of 18Ni300 die steel of Example 1, Comparative Example 1 and Comparative Example 3 of the present invention, wherein 101 represents Example 1, 102 represents Comparative Example 3, and 103 represents Comparative Example 1;
[0026] Figure 5 This is a scanning electron microscope image of the microstructure of the 18Ni300 die steel prepared in Example 1 of the present invention;
[0027] Figure 6 This is a scanning electron microscope image of the bonding interface in the microstructure of the 18Ni300 die steel prepared in Example 1 of the present invention;
[0028] Figure 7 18Ni300 die steel tensile engineering stress-strain curves of Example 1, Example 2 and Comparative Example 1 of the present invention, wherein 101 represents Example 1, 102 represents Example 2, and 103 represents Comparative Example 1;
[0029] Figure 8 This is a scanning electron microscope image of the tensile fracture of the 18Ni300 die steel prepared in Example 1 of the present invention;
[0030] Fig. 9 This is a scanning electron microscope image of the impact fracture of the 18Ni300 die steel prepared in Example 1 of the present invention;
[0031] Fig.10 X-ray diffraction spectra of 18Ni300 die steels prepared in Example 3, Comparative Example 1 and Comparative Example 5 of the present invention, wherein 101 represents Example 3, 102 represents Comparative Example 5, and 103 represents Comparative Example 1;
[0032] Fig.11 This is a scanning electron microscope image of the microstructure of the 18Ni300 die steel prepared in Example 3 of the present invention;
[0033] Fig.12 This is a scanning electron microscope image of the bonding interface in the microstructure of the 18Ni300 die steel prepared in Example 3 of the present invention;
[0034] Fig.13 This is a scanning electron microscope image of the microstructure of the 18Ni300 die steel prepared in Comparative Example 1 of the present invention;
[0035] Fig.14 This is a scanning electron microscope image of the microstructure of the 18Ni300 die steel prepared in Comparative Example 6 of the present invention;
[0036] Fig.15 This is a scanning electron microscope image of the microstructure of the 18Ni300 die steel prepared in Comparative Example 7 of the present invention. DETAILED DESCRIPTION
[0037] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0038] The method for improving the toughness of 18Ni300 die steel produced by additive manufacturing provided by the present invention is described in detail below.
[0039] At present, the room temperature tensile strength of 18Ni300 mold steel formed by laser powder bed fusion can reach 1900-2000MPa after heat treatment, but its toughness is too low and the elongation after fracture is usually less than 5%, which seriously restricts its practical application.
[0040] Based on this, the inventor of the present application creatively proposed a method for improving the toughness of 18Ni300 die steel by adding high melting point spherical metal or alloy powder, which includes the following steps: additively manufacturing composite powder by laser powder bed melting process, followed by heat treatment.
[0041] The composite powder includes 3wt% to 6wt% of high melting point spherical metal or alloy powder, and the remainder is 18Ni300 powder.
[0042] In some optional embodiments, the amount of high melting point spherical metal or alloy powder contained in the composite powder can be 3wt%, 3.5wt%, 4wt%, 4.5wt%, 5wt%, 5.5wt% or 6wt%, etc., or other values within the range of 3wt% to 6wt%. In some more preferred embodiments, the amount of high melting point spherical metal or alloy powder contained in the composite powder is 3wt%.
[0043] It should be noted that the addition amount of high melting point spherical metal or alloy powder has a great influence on the performance of 18Ni300 die steel. If the addition amount is too small, the γ austenite content cannot be significantly improved, and the toughness cannot be effectively improved. If the addition amount is too large, although the γ austenite content is significantly improved, and even the microstructure is mainly γ austenite, the excessive reduction of the α martensite content will greatly reduce the strength of the material, and the high-strength performance characteristics of the die steel itself cannot be reflected, thereby limiting its application field. Therefore, the preferred mass ratio of 18Ni300 powder to high melting point spherical metal or alloy powder in this application is 94:6 to 97:3, and more preferably 97:3.
[0044] In the present invention, the high melting point spherical metal or alloy powder includes pure Mo powder or WC powder with a sphericity of not less than 95%. More preferably, pure Mo powder or WC powder with a sphericity of not less than 95% and few defects is used. In some preferred embodiments, the high melting point spherical metal or alloy powder is an ultra-high spherical pure Mo and WC powder prepared by a radio frequency plasma powder making system. In some more preferred embodiments, the composite powder is composed of 18Ni300 powder and pure Mo powder with a sphericity of not less than 95% and few defects, which can be more conducive to improving the toughness of 18Ni300 die steel than the composite powder composed of 18Ni300 powder and WC powder.
[0045] In some optional embodiments, in the present invention, the particle sizes of the 18Ni300 powder and the high melting point spherical metal or alloy powder are independently 15 μm to 53 μm.
[0046] It should be noted that the sphericity of pure Mo or WC powder also has a great influence on the performance of 18Ni300 die steel. If the sphericity of pure Mo or WC powder is too poor, it will lead to poor interface bonding between the partially melted particles in the microstructure and the matrix (formed by 18Ni300 powder), and sometimes there will be obvious cracks, which will affect the overall mechanical properties of the die steel material including strength and plasticity. Therefore, the invention of this application selects ultra-high spherical pure Mo and WC powders prepared by radio frequency plasma powder making system, and the powder sphericity rate generally exceeds 95%.
[0047] In some optional embodiments, the conditions for additive manufacturing may include: 150W~350W (such as 150W, 200W, 250W, 300W or 350W, etc.), a scanning speed of 700mm / s~1500mm / s (such as 700mm / s, 1000mm / s, 1200mm / s or 1500mm / s, etc.), a scanning spacing of 0.06mm~0.1mm (such as 0.06mm, 0.08mm or 0.1mm, etc.), and a powder laying thickness of 0.03mm~0.05mm (such as 0.03mm, 0.04mm or 0.05mm, etc.).
[0048] In some optional embodiments, the heat treatment may include: treating at 470°C to 530°C (such as 470°C, 480°C, 490°C, 500°C, 510°C, 520°C or 530°C, etc.) for 4h to 8h (such as 4h, 5h, 6h, 7h or 8h, etc.), followed by air cooling. In some preferred embodiments, the heat treatment is treated at 490°C for 6h, followed by air cooling.
[0049] As mentioned above, by adding a specific content of pure Mo powder or spherical WC powder with high sphericity to 18Ni300 powder, the toughness of 18Ni300 mold steel can be significantly improved after laser powder bed melting forming and heat treatment under the above conditions. Specifically, through the above method, on the one hand, the content of γ austenite in the microstructure of the obtained 18Ni300 mold steel can be significantly increased, and the high content of γ austenite can ensure the high toughness of 18Ni300 mold steel; on the other hand, a certain amount of micron-scale partially melted particles (such as Mo particles or W2C particles) with good interface bonding (diffusion type) can be present in the microstructure of the obtained 18Ni300 mold steel, and a large number of nano-scale strengthening phases are precipitated, thereby ensuring the high strength of 18Ni300 mold steel.
[0050] In the present invention, the 18Ni300 die steel contains both γ austenite and α martensite, wherein the content of γ austenite is not less than 9%. In some typical embodiments, the content of γ austenite in the 18Ni300 die steel is 9.3% to 17.1%, while the content of γ austenite in the conventional additively manufactured 18Ni300 die steel is about 4.6%. That is, the 18Ni300 die steel in the present invention has a higher γ austenite content than the conventional additively manufactured 18Ni300 die steel, and in addition, the α martensite content is reduced.
[0051] The 18Ni300 die steel of the present invention also contains nano-scale strengthening phases. For example, a large number of nano-scale Cu-rich precipitates and carbides (such as M6C carbides and hardening phases σ, etc.) will precipitate in the 18Ni300 die steel, as well as Mo-rich precipitates formed by Mo diffused into the matrix, which can improve the high strength of the material.
[0052] The 18Ni300 die steel of the present invention also contains micrometer-scale partially melted high-melting-point spherical metal or alloy particles (such as spherical Mo particles or W2C particles). The interface between the partially melted high-melting-point spherical metal or alloy particles and the matrix is diffusely bonded, there is obvious element diffusion behavior, and the particle surface has an element transition layer.
[0053] The 18Ni300 die steel provided by the invention has a room temperature elongation after fracture of 7.6% to 12.2% and an impact toughness of 24.4 J / cm 2 ~37.5J / cm 2 , the tensile strength is 1612MPa~1958MPa, and the yield strength is 1403MPa~1823MPa. Compared with the conventional 18Ni300 die steel manufactured by additive manufacturing, the 18Ni300 die steel provided by the present invention can have higher toughness while ensuring strength, and can effectively solve the problem of poor plasticity of die steel.
[0054] In addition, the 18Ni300 die steel in the present invention can be used in die for automobiles, electronics, home appliances, plastics, rubber and the like.
[0055] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.
[0056] The spherical 18Ni300 die steel powder in the following examples and comparative examples is prepared by vacuum gas atomization, and the high melting point spherical Mo and WC powders are prepared by radio frequency plasma powder making system. Among them, the particle size of 18Ni300 powder is 15μm to 53μm, and its scanning electron microscope image is as follows Figure 1 As shown, the particle size of Mo and WC powders is also 15μm to 53μm, and the sphericity is greater than 95%. The scanning electron microscope images are shown in Figure 2 and 3 shown.
[0057] The room temperature tensile mechanical properties and impact toughness of the 18Ni300 die steel obtained in the following embodiments and comparative examples are tested in accordance with GB / T 228.1-2021 and GB / T 229-2020, respectively.
[0058] Example 1
[0059] This embodiment provides a 18Ni300 die steel, and the preparation method thereof includes:
[0060] S1: 18Ni300 powder and pure Mo powder were mechanically mixed in a double cone high-efficiency mixer at a mass ratio of 97:3 for 6 h to obtain Mo / 18Ni300 composite powder.
[0061] S2: The composite powder is additively manufactured by laser powder bed fusion process. The process parameters of the laser powder bed fusion process are: laser power 300W, scanning speed 1000mm / s, scanning spacing 0.10mm, and powder thickness 0.05mm.
[0062] S3: heat treating the mold steel obtained by additive manufacturing in a heat treatment furnace, followed by air cooling. The heat treatment conditions are: temperature 490° C., time 6 h.
[0063] The X-ray diffraction spectrum of the 18Ni300 die steel obtained in this embodiment is as follows: Figure 4 As shown by Figure 4 It can be seen that although the microstructure of the 18Ni300 die steel is still mainly α martensite, the content of γ austenite has reached 10.4%.
[0064] The scanning electron microscope image of the microstructure of the 18Ni300 die steel obtained in this embodiment is as follows: Figure 5 As shown, the scanning electron microscope image of the bonding interface in the microstructure of the 18Ni300 die steel obtained in this embodiment is as follows Figure 6 As shown, Figure 5 and Figure 6 The white particles in the figure are a certain amount of partially melted spherical Mo particles observed in the backscattering mode, indicating that the interface between the partially melted Mo particles and the matrix presents a good diffusion-type bonding.
[0065] The tensile engineering stress-strain curve of the 18Ni300 die steel obtained in this embodiment is as follows: Figure 7 As shown by Figure 7 It can be seen that the room temperature tensile strength of the mold steel is 1958MPa, the yield strength is 1823MPa, the elongation after fracture is 10.2%, and the impact toughness is 33.3J / cm 2 .
[0066] The scanning electron microscope image of the tensile fracture of the 18Ni300 die steel obtained in this embodiment is as follows: Figure 8 As shown, the scanning electron microscope image of the impact fracture of the 18Ni300 die steel is as follows Fig. 9 As shown, Figure 8 and Fig. 9 The room temperature fracture morphology shows that both the tensile fracture and impact fracture of the die steel present the characteristics of ductile fracture, with a large number of deep dimples.
[0067] Example 2
[0068] The difference between this embodiment and embodiment 1 is that the mass ratio of 18Ni300 powder to pure Mo powder in the Mo / 18Ni300 composite powder is 94:6.
[0069] After testing, the microstructure of the 18Ni300 die steel obtained in this embodiment is still mainly α martensite, but the γ austenite content has reached 16.2%. The room temperature tensile strength of the 18Ni300 die steel obtained in this embodiment is 1789MPa, the yield strength is 1514MPa, the elongation after fracture is 12.2%, and the impact toughness is 37.5J / cm 2 .
[0070] Example 3
[0071] This embodiment provides a 18Ni300 die steel, and the preparation method thereof includes:
[0072] S1: 18Ni300 powder and WC powder were mechanically mixed in a double cone high-efficiency mixer at a mass ratio of 97:3 for 6 h to obtain WC / 18Ni300 composite powder.
[0073] S2: The composite powder is additively manufactured by laser powder bed fusion process. The process parameters of the laser powder bed fusion process are: laser power 300W, scanning speed 1000mm / s, scanning spacing 0.10mm, and powder thickness 0.05mm.
[0074] S3: heat treating the mold steel obtained by additive manufacturing in a heat treatment furnace, followed by air cooling. The heat treatment conditions are: temperature 490° C., time 6 h.
[0075] The X-ray diffraction spectrum of the 18Ni300 die steel obtained in this embodiment is as follows: Fig.10 As shown by Fig.10 It can be seen that although the microstructure of the 18Ni300 die steel is still mainly α martensite, the γ austenite content has reached 9.3%.
[0076] The scanning electron microscope image of the microstructure of the 18Ni300 die steel obtained in this embodiment is as follows: Fig.11 As shown, the scanning electron microscope image of the bonding interface in the microstructure of the 18Ni300 die steel obtained in this embodiment is as follows Fig.12 As shown, Fig.11 and Fig.12 The white particles in the figure are a certain amount of partially melted spherical W2C particles observed in the backscattering mode, indicating that the interface between the partially melted W2C particles and the matrix presents a good diffusion-type bonding.
[0077] The tensile engineering stress-strain curve of the 18Ni300 die steel obtained in this embodiment is also shown in Figure 7 As shown by Figure 7It can be seen that the room temperature tensile strength of the mold steel is 1171MPa, the yield strength is 1492MPa, the elongation after fracture is 7.6%, and the impact toughness is 24.4J / cm 2 .
[0078] Example 4
[0079] The difference between this embodiment and embodiment 3 is that the mass ratio of 18Ni300 powder to WC powder in the WC / 18Ni300 composite powder is 94:6.
[0080] After testing, the microstructure of the 18Ni300 die steel obtained in this embodiment is still mainly α martensite, but the γ austenite content has reached 17.1%. The room temperature tensile strength of the 18Ni300 die steel obtained in this embodiment is 1612MPa, the yield strength is 1403MPa, the elongation after fracture is 8.3%, and the impact toughness is 28.6J / cm 2 .
[0081] Example 5
[0082] The difference between this embodiment and embodiment 1 is that the process parameters of the laser powder bed melting process in the S2 process are: laser power 150W, scanning speed 700mm / s, scanning spacing 0.10mm, powder thickness 0.03mm; the heat treatment conditions in the S3 process are: temperature 470℃, time 8h.
[0083] After testing, the microstructure of the 18Ni300 die steel obtained in this embodiment is still mainly α martensite, but the γ austenite content has reached 9.5%. The room temperature tensile strength of the 18Ni300 die steel obtained in this embodiment is 1768MPa, the yield strength is 1467MPa, the elongation after fracture is 9.4%, and the impact toughness is 28.5J / cm 2 .
[0084] Example 6
[0085] The difference between this embodiment and embodiment 1 is that the process parameters of the laser powder bed melting process in the S2 process are: laser power 350W, scanning speed 1500mm / s, scanning spacing 0.06mm, powder thickness 0.05mm; the heat treatment conditions in the S3 process are: temperature 530℃, time 4h.
[0086] After testing, the microstructure of the 18Ni300 die steel obtained in this embodiment is still mainly α martensite, but the γ austenite content has reached 11.3%. The room temperature tensile strength of the 18Ni300 die steel obtained in this embodiment is 1864MPa, the yield strength is 1614MPa, the elongation after fracture is 11.0%, and the impact toughness is 34.8J / cm 2 .
[0087] Comparative Example 1
[0088] This comparative example provides an 18Ni300 die steel material, whose preparation method and heat treatment method are the same as those of Example 1 and Example 2, except that a single conventional 18Ni300 powder is used for additive manufacturing.
[0089] The X-ray diffraction spectrum of the 18Ni300 die steel obtained in this comparative example is as follows: Figure 4 and Fig.10 The scanning electron microscope image of the microstructure is shown in Fig.13 As shown by Figure 4 , Fig.10 and Fig.13 It can be seen that the microstructure of the 18Ni300 die steel prepared in this comparative example is mainly composed of typical α martensite, and the content of γ austenite is only 4.6%.
[0090] The tensile engineering stress-strain curve of 18Ni300 die steel obtained in this comparative example is also as shown in Figure 7 As shown by Figure 7 It can be seen that the room temperature tensile strength of the mold steel is 1904MPa, the yield strength is 1840MPa, the elongation after fracture is only 4.1%, and the impact toughness is 20.2J / cm 2 .
[0091] Comparative Example 2
[0092] The difference between this comparative example and Example 1 is that the mass ratio of 18Ni300 powder to pure Mo powder in the Mo / 18Ni300 composite powder is 99:1.
[0093] After testing, the microstructure of the 18Ni300 die steel obtained in this comparative example is still mainly α martensite, the γ austenite content is only 4.9%, and there are a small amount of partially melted Mo particles. The room temperature tensile strength of the 18Ni300 die steel obtained in this comparative example is 2183MPa, the yield strength is 2095MPa, the elongation after fracture is only 4.9%, and the impact toughness is 21.8J / cm 2 .
[0094] Comparative Example 3
[0095] The difference between this comparative example and Example 1 is that the mass ratio of 18Ni300 powder to pure Mo powder in the Mo / 18Ni300 composite powder is 90:10.
[0096] The X-ray diffraction spectrum of the 18Ni300 die steel obtained in this comparative example is as follows: Figure 4As shown, the microstructure of the 18Ni300 die steel obtained in this comparative example has been transformed into mainly γ austenite, with a content of 58.8%, while the α martensite content has dropped to 41.2%, and there are a large number of partially melted Mo particles. The room temperature tensile strength of the 18Ni300 die steel obtained in this comparative example is only 1039MPa, the yield strength is only 792MPa, the elongation after fracture is 28.0%, and the impact toughness is 44.6J / cm 2 .
[0097] Comparative Example 4
[0098] The difference between this comparative example and Example 3 is that the mass ratio of 18Ni300 powder to WC powder in the WC / 18Ni300 composite powder is 99:1.
[0099] After testing, the microstructure of the 18Ni300 die steel obtained in this comparative example is still mainly α martensite, the γ austenite content is only 5.0%, and there are a small amount of partially melted W2C particles. The room temperature tensile strength of the 18Ni300 die steel is 1978MPa, the yield strength is 1799MPa, the elongation after fracture is only 4.4%, and the impact toughness is 20.4J / cm 2 .
[0100] Comparative Example 5
[0101] The difference between this comparative example and Example 3 is that the mass ratio of 18Ni300 powder to WC powder in the WC / 18Ni300 composite powder is 90:10.
[0102] The X-ray diffraction spectrum of the 18Ni300 die steel obtained in this comparative example is as follows: Fig.10 As shown, the microstructure of the 18Ni300 die steel obtained in this comparative example has been transformed into mainly γ austenite, with a content of 75.6%, while the α martensite structure has dropped to 24.4%, and there are a large number of partially melted W2C particles. The room temperature tensile strength of the 18Ni300 die steel is only 1159MPa, the yield strength is only 825MPa, the elongation after fracture is 6.1%, and the impact toughness is 54.3J / cm 2 .
[0103] Comparative Example 6
[0104] The difference between this comparative example and Example 1 is that the sphericity of the pure Mo powder is only 90%.
[0105] According to the test, although the microstructure of the 18Ni300 die steel prepared in this comparative example is still mainly composed of α martensite, the content of γ austenite reaches 10.0%.
[0106] The scanning electron microscope image of the microstructure of the 18Ni300 die steel obtained in this comparative example is as follows: Fig.14 As shown by Fig.14 It can be seen that the metallurgical bonding at the interface between some partially melted Mo particles and the matrix is not very good, that is, there are a small amount of defects such as slag inclusions and microcracks, and there are defects such as holes inside the particles.
[0107] The room temperature tensile strength of the 18Ni300 die steel prepared in this comparative example is 1424MPa, the yield strength is 1137MPa, the elongation after fracture is 4.2%, and the impact toughness is 18.4J / cm 2 .
[0108] Comparative Example 7
[0109] The difference between this comparative example and Example 3 is that the sphericity of the WC powder is only 80%.
[0110] According to the test, although the microstructure of the 18Ni300 die steel prepared in this comparative example is still mainly composed of α martensite, the content of γ austenite reaches 8.7%.
[0111] The scanning electron microscope image of the microstructure of the 18Ni300 die steel obtained in this comparative example is as follows: Fig.15 As shown by Fig.15 It can be seen that the metallurgical bonding at the interface between a certain amount of partially melted W2C particles and the matrix is not good, that is, there are a large number of obvious defects such as cracks and unfused.
[0112] The room temperature tensile strength of the 18Ni300 die steel prepared in this comparative example is 1364MPa, the yield strength is 1054MPa, the elongation after fracture is 2.4%, and the impact toughness is 14.2J / cm 2 .
[0113] The test results of the above embodiments and comparative examples are summarized in Table 1.
[0114] Table 1 Performance test results
[0115]
[0116] According to the data in Table 1, the room temperature elongation after fracture of the 18Ni300 die steel prepared in Examples 1 to 6 of the present invention is 7.6% to 12.2%, and the impact toughness is 24.4 J / cm 2 ~37.5J / cm 2 The tensile strength is 1612MPa~1958MPa, and the yield strength is 1403MPa~1823MPa. It can have high toughness while ensuring strength.
[0117] Compared with Example 1, the Mo content in Comparative Example 2 is too low (1%), and the γ-austenite content is not significantly increased, resulting in an insignificant increase in toughness. The elongation after fracture and impact toughness are only increased to 4.1% and 21.8 J / cm, respectively. 2 In Comparative Example 3, the Mo content is too high (10%), the γ austenite content is greatly increased (58.8%), and the corresponding α martensite content is greatly reduced (41.2%), resulting in a significant reduction in strength, and the tensile strength is only 1039MPa. Similarly, compared with Example 3, the WC content in Comparative Examples 4 and 5 is too low or too high, and the plasticity of the mold steel obtained by the same preparation process is not significantly improved or the strength is greatly reduced.
[0118] Compared with Example 1, the sphericity of the pure Mo powder of Comparative Example 6 is lower (90%), resulting in a small amount of slag inclusions, microcracks and other defects at the interface between some partially melted particles and the matrix, and there are also defects such as holes inside the particles, which further affects the overall mechanical properties of the 18Ni300 die steel. Similarly, compared with Example 3, the sphericity of the WC powder of Comparative Example 7 is lower (80%), resulting in a large number of cracks, lack of fusion and other obvious defects at the interface between a certain amount of partially melted particles and the matrix, which further affects the overall mechanical properties of the 18Ni300 die steel.
[0119] In summary, the 18Ni300 die steel provided by the present invention can have higher toughness while ensuring strength, and can effectively solve the problem of poor plasticity of die steel.
[0120] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for improving the toughness of 18Ni300 die steel for additive manufacturing, characterized in that: The following steps are involved: Additive manufacturing of composite powders using laser powder bed fusion followed by heat treatment; The composite powder comprises 3wt% to 6wt% of high melting point spherical metal or alloy powder, and the balance is 18Ni300 powder; the high melting point spherical metal or alloy powder comprises pure Mo powder or WC powder with a sphericity of not less than 95%.
2. The method according to claim 1, characterized in that The composite powder consists of 18Ni300 powder and pure Mo powder with a sphericity of not less than 95%.
3. The method according to claim 1, characterized in that The particle sizes of the 18Ni300 powder and the high melting point spherical metal or alloy powder are independently 15 μm to 53 μm.
4. The method according to claim 1, characterized in that: The conditions for additive manufacturing include: laser power of 150W to 350W, scanning speed of 700mm / s to 1500mm / s, scanning spacing of 0.06mm to 0.10mm, and powder thickness of 0.03mm to 0.05mm.
5. The method according to claim 1, characterized in that Heat treatment includes: Treat at 470℃~530℃ for 4h~8h, then air cool.
6. The method according to claim 5, characterized in that The heat treatment was carried out at 490 °C for 6 h, followed by air cooling.
7. The method according to any one of claims 1 to 6, characterized in that: The 18Ni300 die steel contains both γ austenite and α martensite, wherein the content of γ austenite is not less than 9%.
8. The method according to claim 7, characterized in that The content of γ austenite in the 18Ni300 die steel is 9.3% to 17.1%.
9. The method according to claim 7, characterized in that: The 18Ni300 die steel also contains a nano-scale strengthening phase.
10. The method according to claim 1, characterized in that The room temperature elongation of the 18Ni300 die steel is 7.6% to 12.2%, and the impact toughness is 24.4 J / cm 2 ~37.5J / cm 2 , the tensile strength is 1612MPa~1958MPa, and the yield strength is 1403MPa~1823MPa.